User Satisfaction and Application Usage of PA'KEPO: A UTAUT 2 Model Analysis - Agam, Padel Mohammad; Negara, Edi Surya; Andryani, Ria (Universitas Bina Darma, 2024)
The PA'KEPO (Payo jadi Keluargo Polisi) application is a mobile Android application owned by Polda Sumsel for the recruitment process of police members. This study aims to evaluate user satisfaction and the use of the PA'KEPO application by applying the Unified Theory of Acceptance and Use of Technology (UTAUT) 2 model with the addition of the Perceived Trust variable, which represents users' trust in the security and reliability of the application, enhancing users' intention to use the application and impacting actual usage behavior. The analysis of the relationships between variables employs the Structural Equation Modeling (SEM) approach to test the complex relationships between latent variables, allowing for the analysis of data with diverse scales. The research results indicate that the majority of respondents experienced a high level of satisfaction with the PA'KEPO application. The most influential variables—Effort Expectancy, Perceived Trust, Hedonic Motivation, Habit, and Behavioral Intention—significantly affect Use Behavior. Based on these findings, it is recommended that Polda Sumsel continue to encourage the use of the PA'KEPO application by optimizing the variables that have not yet shown significant effects. Improvement recommendations include evaluating and enhancing the application's functionality in line with the daily needs of its users.